Persistence in Science Play and Gender: Findings from Early Childhood Classrooms in Ireland. Issue 4 (19th May 2023) - Gilligan, Therese; McNally, Sinéad; Lovett, Judy; Farell, Therese; Kumar, Sona; McLoughlin, Eilish; Corriveau, Kathleen
ABSTRACT: The under-representation of women in science disciplines is a persistent problem for workplaces and educational policy. Girls may start to disengage early from science subjects, partly due to cultural stereotypes around science and gender. Early language interventions which introduce science activities in terms of action (or process) versus identity (or fixed ability) suggest that language impacts girls' early engagement in science tasks. Research Findings: This study tested young children's (N = 116) persistence on a digital "sink-or-float" game in early childhood classrooms in primary schools in Ireland (elementary school, aged four to six years). Children found the task difficult with lower accuracy scores for girls. Controlling for accuracy, boys persisted on the task for longer than girls. Introducing the game in terms of action versus identity did not impact children's persistence on the activity. Practice or Policy: Gender differences in science play are discussed in terms of the generally low levels of accuracy on the task and the potential role of negative feedback on persistence among boys and girls. Future directions for research are highlighted, including a focus on early science engagement for young children.